2017
DOI: 10.1021/acs.energyfuels.7b00908
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of the Transformation of Oil Shale with Fracturing Fluids under Microwave Heating in the Presence of Nanoparticles

Abstract: Traditional methods of exploiting oil shale such as mining or in situ electric heating cause environmental pollution, and they have huge energy losses and high costs. These problems can be solved by combining microwave heating with hydraulic fracturing for the in situ exploitation of oil shale. In this study, an experimental microwave apparatus was manufactured for laboratory experiments. Different weight proportions of iron oxide nanoparticles (0.1, 0.5, and 1 wt %), microwave output power (600, 800, and 1000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 43 publications
0
21
0
Order By: Relevance
“…So MW-generated oils which were rich in p-Xylene, indene, naphthalene and other aromatic hydrocarbons were desirable for obtaining recoverable energy and chemicals. It was also concluded in other report that microwave irradiation can both crack the chemical bonds in large molecules, such as long-chain, branched-chain, and heterocyclic compounds and convert them into small-molecule fractions [45]. This may contribute to explaining the composition difference between MW and CV pyrolysis.…”
Section: Gc-ms Analysismentioning
confidence: 66%
“…So MW-generated oils which were rich in p-Xylene, indene, naphthalene and other aromatic hydrocarbons were desirable for obtaining recoverable energy and chemicals. It was also concluded in other report that microwave irradiation can both crack the chemical bonds in large molecules, such as long-chain, branched-chain, and heterocyclic compounds and convert them into small-molecule fractions [45]. This may contribute to explaining the composition difference between MW and CV pyrolysis.…”
Section: Gc-ms Analysismentioning
confidence: 66%
“…Bera and Babadagli confirmed the positive effect of microwave heating on the viscosity reduction of heavy oil . According to the development of oil shale, Yang proposed a microwave heating method with hydraulic fracturing for the in situ exploitation of oil shale . Moreover, lab experiments proved that oil shale could be efficiently transform into shale oil with high production and high quality under microwave irradiation.…”
Section: Introductionmentioning
confidence: 95%
“…8 According to the development of oil shale, Yang proposed a microwave heating method with hydraulic fracturing for the in situ exploitation of oil shale. 9 Moreover, lab experiments proved that oil shale could be efficiently transform into shale oil with high production and high quality under microwave irradiation. It only took 3 minutes for oil shale to reach approximately 1000°C under microwave heating in the existence of microwave absorbent conducted by Hascakir, showing the great function of microwave.…”
Section: Introductionmentioning
confidence: 99%
“…Since investigations conducted by Yang et al 46 showed that output power of 1000 W inevitably reduced the production of shale oil due to secondary reactions at high temperature, there are both advantages and disadvantages to applying high output power for the in situ exploitation of oil shale. The production and quality of shale oil and gas should also be considered at the same time.…”
Section: Potential Application Of Microwave Energy For the Exploitamentioning
confidence: 99%
“…The production and quality of shale oil and gas should also be considered at the same time. Since investigations conducted by Yang et al 46 showed that output power of 1000 W inevitably reduced the production of shale oil due to secondary reactions at high temperature, there are both advantages and disadvantages to applying high output power for the in situ exploitation of oil shale. Moreover, in order to upgrade microwave heating to an industrial scale, several potential challenges and difficulties including choosing optimal heating parameters, designing an industrial microwave generator and analyzing economic feasibility should also be overcome in the future.…”
Section: Potential Application Of Microwave Energy For the Exploitamentioning
confidence: 99%